Evaluation of a Predictive Control Applied to the Tracking of the Trajectory of a Manipulator Robot with 3-Dof - Urrea-Onate, E; Kern-Molina, J (Institute of Electrical and Electronics Engineers Inc., 2021)
In the field of robotics, one of the problems is the error produced by the controllers in the follow up of a certain trajectory by the manipulator, for this reason the objective of this research is based on the execution a Predictive Controller for a robot of three degrees of freedom. The study presented in this document is mainly based on an investigation of the structure and the different elements involved in model based predictive control; the same ones that were applied to the control of a 3-DOF manipulator, for which it was necessary to analyze its kinematics and dynamics, which allowed the implementation and realization of its respective simulation with the help of Simulink from MatLab. To analyze the behavior of the manipulated, a trajectory was implemented, which allowed to analyze the error between the desired trajectory and the one carried out by the robot. In order to improve the predictive controller and reduce the error, the behavior was analyzed for different parameters of the prediction horizon, control intervals and control horizon, as well as the linearization of the plant. © 2021 IEEE.